PENGARUH KOMUNIKASI DAN TEAMWORK TERHADAP KINERJA KARYAWAN MARKETING SUPPORT DI PT. PUPUK SRIWIDJAJA PALEMBANG - Indria Elvina; Heriyanto, Heriyanto (Bajang Institute, 2024)
Teamwork generates positive synergies through coordinated efforts. This has the understanding that the performance achieved by a team is better than the performance per individual in an organization or a company. From all the notions of teamwork that have been stated, it can be concluded that teamwork is the most effective way to unite all employees in carrying out their tasks to achieve company goals with better results. This type of research uses quantitative research. This qualitative approach is carried out to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs, and perceptions. The result of the analysis is communication at the Marketing Support office at PT. Pupuk Sriwidjaja Palembang has a significant effect on employee performance. Indicators as supervision/coordination, motivation, as disseminators or sharers of information, and display feelings and emotions.